2019
DOI: 10.1111/jcmm.14713
|View full text |Cite
|
Sign up to set email alerts
|

Astilbin prevents bone loss in ovariectomized mice through the inhibition of RANKL‐induced osteoclastogenesis

Abstract: Osteoporosis is the most common osteolytic disease characterized by excessive osteoclast formation and resultant bone loss, which afflicts millions of patients around the world. Astilbin, a traditional herb, is known to have anti‐inflammatory, antioxidant and antihepatic properties, but its role in osteoporosis treatment has not yet been confirmed. In our study, astilbin was found to have an inhibitory effect on the RANKL‐induced formation and function of OCs in a dose‐dependent manner without cytotoxicity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Bisphosphonates and denosumab have been shown to give rise to osteonecrosis of the jaw ( Hamadeh et al, 2015 ; Khan et al, 2015 ; Boquete-Castro et al, 2016 ), and teriparatide can increase the risk of osteosarcoma ( Gilsenan et al, 2018 ). Compared with synthetic chemicals, natural compounds seem to have an advantage in terms of safety, some of which inhibit bone resorption and bone loss in OVX mice ( Jin et al, 2019 ; Zhou et al, 2019 ; Zhou et al, 2020 ). In this study, we explored the therapeutic effects of NOT on osteoclasts and OVX-mediated bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates and denosumab have been shown to give rise to osteonecrosis of the jaw ( Hamadeh et al, 2015 ; Khan et al, 2015 ; Boquete-Castro et al, 2016 ), and teriparatide can increase the risk of osteosarcoma ( Gilsenan et al, 2018 ). Compared with synthetic chemicals, natural compounds seem to have an advantage in terms of safety, some of which inhibit bone resorption and bone loss in OVX mice ( Jin et al, 2019 ; Zhou et al, 2019 ; Zhou et al, 2020 ). In this study, we explored the therapeutic effects of NOT on osteoclasts and OVX-mediated bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds with a broad spectrum of biological activity and limited side-effects have become the main targets of our research. There have been many studies on the treatment of osteoporosis using natural compounds (7)(8)(9) that have provided us with a reliable theoretical and technological basis for our exploration into the field.…”
Section: Introductionmentioning
confidence: 99%
“…Although these drugs showed inhibitory effect on osteoclast activity, they had no effect on osteogenic activity. [14][15][16] Simply reducing osteoclast activity may interfere with bone formation, reduce bone transformation and bring side effects such as mandibular osteonecrosis. Studies have shown that the proliferation of early osteoclasts requires the activation of β-catenin; however, the activated β-catenin inhibits the differentiation of osteoclasts.…”
mentioning
confidence: 99%